DETERMINANTS OF FINANCIAL FRAUD REPORTING: EVIDENCE FROM THE HEALTH SECTOR IN INDONESIA - Mohamad Zulman Hakim; Chika Amanda; Arian Firmansyah; Pingkan Pramudita Putri (PT. ZILLZELL MEDIA PRIMA, 2026)
This study investigates the determinants of financial fraud reporting (FFR) by examining the influence of corporate governance and financial performance indicators. Using a balanced panel dataset of 15 firms in healthcare sector over 4 years (2021–2024), this research employs panel data regression analysis through three models: Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). Variables analyzed include Return on Assets (ROA), asset change (ACHANGE), leverage, ownership structure (OSHIP), corporate internal disclosure (CID), growth potential (GP), state-owned enterprise status (SOE), CEO duality, board independence (BDOUT), number of independent oversight institutions (NOI), chairman audit committee (CHAUD), and CEO political connections (CEOPIC). Model selection was determined using the Chow test, Hausman test, and Lagrange Multiplier (LM) test. The REM was chosen as the most appropriate model. The results show that NOI, ACHANGE, and LEVERAGE significantly influence FFR, while other governance-related variables show insignificant effects. This suggests that internal oversight mechanisms and financial leverage play a more prominent role in detecting and preventing fraudulent activities than ownership or governance structures alone. The findings provide evidence for regulators and corporate boards to strengthen internal controls and risk assessment mechanisms to mitigate fraud risks.